Short‐selling and cost of equity: evidence from China. (25th September 2019) - Hu, Ning; Lu, Siqi; Ma, Tao; Ye, Jianfang
Abstract: In this study, we take advantage of the gradual lifting of the short‐selling ban in China and find that firms affected by the lifting of the ban experience a lower cost of equity. In addition, the affected firms also incur less earnings management, higher market liquidity and higher investment efficiency. Further evidence shows that firms' cost of equity increases after their stocks are no longer eligible for short selling. Our inferences are robust to alternative measures of cost of equity, and to using a propensity score‐matched sample. Our study contributes to the literature by providing evidence that short sellers play a monitoring role in the Chinese stock markets and sheds light on the benefits of short selling in emerging markets.